A Study on the Implementation of the Smart City Concept in Indonesia, Study on the Capital City of Jakarta - Yohana Dwi Asima Purba; Riyanto Jayadi (Departement of Mathematics Education, 2023)
Jakarta, as the capital city of Indonesia, shows its seriousness in implementing Smart City technology in its city, namely by building a Jakarta Smart City (JSC). Jakarta Smart City has six indicators that form the basis for the development of Smart City. The six indicators are smart economy, smart people, smart governance, smart mobility, smart environment, and smart living. This study discusses the implementation of the concept of smart city in Jakarta based on the successful of each indicator and discusses about the extent of Smart City in supporting Jakarta’s vision and mission. This paper aims to provide an overview of the successful of smart city implementation in the city of Jakarta, as well as the improvements that needed to be done. This study uses the method of a study literature to get an early picture of the current conditions in Jakarta and Jakarta Smart City, then assessment using survey through interview and questionnaires, and qualitative analysis of descriptive. The result show that the six indicators of Smart City concept have been implemented successfully in the city of Jakarta and in line with the vision and mission of Jakarta. However, improvements in several aspects, as well as support from the citizens and government are deemed.